Dual Role of a Viral Polymerase in Viral Genome Replication and Particle Self-Assembly - Xiaoyu Sun (American Society for Microbiology, 2018)
ABSTRACT Double-stranded RNA (dsRNA) viruses package several RNA-dependent RNA polymerases (RdRp) together with their dsRNA genome into an icosahedral protein capsid known as the polymerase complex. This structure is highly conserved among dsRNA viruses but is not found in any other virus group. RdRp subunits typically interact directly with the main capsid proteins, close to the 5-fold symmetric axes, and perform viral genome replication and transcription within the icosahedral protein shell. In this study, we utilized Pseudomonas phage Φ6, a well-established virus self-assembly model, to probe the potential roles of the RdRp in dsRNA virus assembly. We demonstrated that Φ6 RdRp accelerates the polymerase complex self-assembly process and contributes to its conformational stability and integrity. We highlight the role of specific amino acid residues on the surface of the RdRp in its incorporation during the self-assembly reaction. Substitutions of these residues reduce RdRp incorporation into the polymerase complex during the self-assembly reaction. Furthermore, we determined that the overall transcription efficiency of the Φ6 polymerase complex increased when the number of RdRp subunits exceeded the number of genome segments. These results suggest a mechanism for RdRp recruitment in the polymerase complex and highlight its novel role in virion assembly, in addition to the canonical RNA transcription and replication functions. IMPORTANCE Double-stranded RNA viruses infect a wide spectrum of hosts, including animals, plants, fungi, and bacteria. Yet genome replication mechanisms of these viruses are conserved. During the infection cycle, a proteinaceous capsid, the polymerase complex, is formed. An essential component of this capsid is the viral RNA polymerase that replicates and transcribes the enclosed viral genome. The polymerase complex structure is well characterized for many double-stranded RNA viruses. However, much less is known about the hierarchical molecular interactions that take place in building up such complexes. Using the bacteriophage Φ6 self-assembly system, we obtained novel insights into the processes that mediate polymerase subunit incorporation into the polymerase complex for generation of functional structures. The results presented pave the way for the exploitation and engineering of viral self-assembly processes for biomedical and synthetic biology applications. An understanding of viral assembly processes at the molecular level may also facilitate the development of antivirals that target viral capsid assembly.